2008
DOI: 10.1007/s10750-008-9370-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic pathways for the anaerobic decomposition of Ludwigia inclinata

Abstract: This study is aimed at using kinetic modeling to investigate the yield of mineralization products from anaerobic decomposition of the aquatic macrophyte Ludwigia inclinata. The initial hypothesis was that the decay of different fractions of detritus and the kinetics of gases productions are both positively correlated to temperature. The plants and water samples were collected from a tropical oxbow lake; the anaerobic decomposition was described using incubations maintained at controlled temperatures. The metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
1
0
2
Order By: Relevance
“…Tal combinação deve ter favorecido a produção de CH 4 , pois no intervalo de 10 a 45 ºC a taxa de crescimento da população microbiana duplica a cada 10 °C de aumento na temperatura da água (Rittmann & McCarty, 2001). Em adição, temperaturas maiores que 20 ºC aumentam a solubilização da matéria orgânica (Gujer & Zehnder, 1983), ao mesmo tempo em que favorecem a produção de CH 4 , confirmando que o processo de metanogênese é mais sensível à variação deste parâmetro se comparado aos demais processos de mineralização (Romeiro & Bianchini Jr., 2008;Bianchini Jr. et al, 2010).…”
Section: Resultsunclassified
“…Tal combinação deve ter favorecido a produção de CH 4 , pois no intervalo de 10 a 45 ºC a taxa de crescimento da população microbiana duplica a cada 10 °C de aumento na temperatura da água (Rittmann & McCarty, 2001). Em adição, temperaturas maiores que 20 ºC aumentam a solubilização da matéria orgânica (Gujer & Zehnder, 1983), ao mesmo tempo em que favorecem a produção de CH 4 , confirmando que o processo de metanogênese é mais sensível à variação deste parâmetro se comparado aos demais processos de mineralização (Romeiro & Bianchini Jr., 2008;Bianchini Jr. et al, 2010).…”
Section: Resultsunclassified
“…For an oxbow lake Ballester and Santos (2001) reported maximum rates of gas formation between the 80º and 90º days of incubation, with formation of CO 2 and CH 4 and, in general, prevalence of gas production over consumption. Assays on anaerobic decomposition of Ludwigia sedoides in different temperatures indicated that CO 2 formation were produced from the first day of decomposition; in relation to methanogenesis, this gases formation presented different genesis periods: 15 th day at 29.9 °C and 99 th at 15.0 °C (Romeiro and Bianchini Jr., 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Contudo, em condições anaeróbias, o aumento da temperatura constitui-se num fator extremamente importante para a geração de CH 4 . A esse respeito, verifi cou-se na decomposição de Ludwigia inclinata (Romeiro & Bianchini Jr. 2008) que a produção de metano correspondeu de 0,4 a 9,8% de perda de massa dos detritos em função do aumento da temperatura (de 15 a 30ºC). Os maiores rendimentos de metano em temperaturas mais elevadas também foram observados na decomposição de Egeria najas (CH 4 =13,4% a 18ºC; CH 4 =28,6% a 27ºC) (Bitar et al 2006).…”
Section: -Mineralização Dos Detritos Particulados Refratários (Copr)unclassified